THE LONG VIEW: COMPARING OUTCOMES OF CLASS- AND HOME-BASED PHYSICAL ACTIVITY PROGRAMS FOUR YEARS LATER. (11th November 2018) - Fisher, K; Harrison, E L; Reeder, B A; Sari, N; Chad, K E
Abstract: Both class- and home-based (CB; HB) physical activity programs are effective in increasing functional performance, physical fitness and other health outcomes in older adults. Direct comparisons of program effectiveness have been equivocal and few have examined outcomes beyond the 12-month mark. 50+ in motion was a randomized clinical trial comparing the effectiveness of a CB and HB physical activity program for sedentary older adults with chronic health conditions. The intervention consisted of a 3-month intensive phase and a 9-month follow-up phase. Data were collected from 172 participants at baseline, 3-, 6-, 12-months, and then annually for a total of 48 months. Outcomes included cardiovascular fitness, functional performance, body composition, quality of life, and health services utilization. In both programs, improvements in most outcomes were sustained beyond 12-months with some extended through the entire follow-up period. There were no differences in health services variables between the programs until the final year.